Implementation of Learning Methods Based on Qur'an and Hadith to Enhance Student Competence in the Digital Era - Septa Kurniawan, Andre (Islamic Journal of Teaching and Learning, 2025)
This study addresses the challenge of integrating Islamic pedagogical principles with contemporary digital learning methods to prepare Muslim students for success in the digital era while preserving spiritual and moral grounding. The objective was to evaluate the effectiveness of Qur'an-Hadith-based learning approaches in enhancing cognitive, digital, ethical, creative, and social-emotional competencies. Using a pretest-posttest control group design, the study compared three pedagogical approaches Qur'an-Hadith-based digital learning, conventional digital learning, and traditional Islamic instruction among 900 secondary students from Indonesia, Malaysia, Saudi Arabia, and Turkey. Data were collected using validated instruments, including the Cornell Critical Thinking Test, DigComp 2.2 Framework, Defining Issues Test-2, Torrance Tests of Creative Thinking, and Social-Emotional Competence Questionnaire, complemented by classroom observations and interviews. Results indicated that Qur'an-Hadith-based learning significantly outperformed both comparison groups in all competency domains, with medium-to-large effect sizes. The integration of Qur'anic pedagogical principles with digital technologies not only improved academic performance but also fostered character development. The findings suggest implications for curriculum redesign, teacher preparation, and policy development that incorporate religiously-grounded pedagogical excellence. This study contributes valuable insights for advancing digital education in Muslim educational contexts.